(untitled) (Research, Society and Development, 2022)
The objective of this study was to perform a comparative analysis of the fatigue strength of NiTi instruments in an in vitro model (artificial canal). Ten Hyflex EDM instruments (tip: 10; taper: .05) (Coltene/Whaledent, Altstätten, Switzerland) and ten Bassi LogicTM instruments (tip: 15; taper: .05) (Bassi Endo, Belo Horizonte, Brazil) were used. For the static bending fatigue strength test, we used a stainless-steel artificial canal with a 5-mm curvature radius, 90º curvature, and inner diameter of 1.5 mm. The instruments were run in the artificial canal until the occurrence of fracture. The time was recorded and the number of cycles was calculated. The length of the fragments was measured and three samples from each group were analyzed using scanning electron micrscopy for the characterization of metal fatigue. The data were compared using the nonparametric Man-Whitney test (samples with non-normal distribution), with the significance level set at 5% (p<0.05). Bassi LogicTM instruments tolerated a greater number of cycles compared to the Hyflex EDM (p < 0.05). Significant differences in fragment size were also found between groups (p < 0.05). Mean fragment size was larger among the Hyflex EDM instruments compared to the Bassi LogicTM instruments.The Bassi LogicTM 15.05 exhibited greater fatigue strength in artificial canals with an accentuated curvature compared to Hyflex EDM 10.05.